Manajemen Kesiswaan dalam Peningkatan Etos Kerja OSIS MTS Salafiyah Syafi’iyah Tebuireng Jombang - Zuliani Nurrofiah; Moh. Syamsul Falah (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
Student affairs management plays a crucial role in improving the quality of students, especially in student organization such as OSIS (Student Council). OSIS requires a high work ethic to achieve a good organizational quality. In this article, the researchers conducted a study on student affairs management related to the improvement of work ethic in OSIS at MTs Salafiyah Syafi'iyah Tebuireng. This research adopts a qualitative approach, utilizing data sources from interviews, observations, and documentation. The theoretical framework used in this study is POAC (Planning, Organizing, Actuating, and Controlling). However, there are several factors that hinder the improvement, such as the students' unstable age, which sometimes makes it difficult to follow established rules. Nevertheless, student affairs management has successfully enhanced the work ethic of OSIS at MTs Salafiyah Syafi'iyah Tebuireng in terms of Planning, Organizing, Actuating, and Controlling